High‐risk screening for late‐onset Pompe disease in China: An expanded multicenter study - Jiao, Kexin; Zhu, Bochen; Chang, Xueli; Guo, Junhong; Fu, Jun; Song, Xueqin; Yu, Xuen; Zhang, Xiaoge; Dong, Jihong; Yan, Wang; Luan, Xinghua; Wang, Zhiqiang; et al. (Journal of inherited metabolic disease, 2025)
Late‐onset Pompe disease (LOPD) is caused by a genetic deficiency of the lysosomal enzyme acid alpha‐glucosidase (GAA), leading to progressive limb‐girdle weakness and respiratory impairment. The insidious onset of non‐specific early symptoms often prohibits timely diagnosis. This study aimed to validate the high‐risk screening criteria for LOPD in the Chinese population. A total of 726 patients were included, including 96 patients under 14 years of age. Dried blood spots (DBS) and tandem mass spectrometry (MS/MS) were employed to evaluate serum GAA activity. Forty‐four patients exhibited a decreased GAA activity, 16 (2.2%) of which were confirmed as LOPD by genetic testing. Three previously unreported GAA mutations were also identified. The median diagnostic delay was shortened to 3 years, which excelled the previous retrospective studies. At diagnosis, most patients exhibited impaired respiratory function and/or limb‐girdle weakness. Elevated serum creatine kinase (CK) levels were more frequently observed in patients who manifested before age 16. Overall, high‐risk screening is a feasible and efficient method to identify LOPD patients at an early stage. Patients over 1 year of age with either weakness in axial and/or proximal limb muscles, or unexplained respiratory distress shall be subject to GAA enzymatic test, while CK levels above 2 times the upper normal limit shall be an additional criterion for patients under 16. This modified high‐risk screening criteria for LOPD requires further validation in larger Chinese cohorts.